2012
DOI: 10.3892/ol.2012.972
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ku70 and Bax in epigallocatechin-3-gallate-induced apoptosis of A549 cells in vivo

Abstract: Abstract. EGCG (epigallocatechin-3-gallate), the major catechin found in green tea, has been demonstrated to inhibit proliferation and induce apoptosis in a number of types of tumors. Recent studies reveal that EGCG has various anticancer effects. This study investigated a further possible molecular mechanism of the anticancer effects of EGCG in murine lung cancer xenografts. In the study, A549 human lung cancer cells were injected into nude mice. Tumor volume was used to measure cancer cell growth. The weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…These results are consistent with previous studies. [18][19][20] in which EGCG showed antiproliferative effects on lung cancer tumor in vivo, but failed to induce tumor regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with previous studies. [18][19][20] in which EGCG showed antiproliferative effects on lung cancer tumor in vivo, but failed to induce tumor regression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a limited number of papers have reported effects of EGCG on lung cancer tumor growth in vivo. [18][19][20] Only one paper has reported an effect of EGCG on A549 tumor growth in vivo. 20)…”
mentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG) is a water-soluble catechin, which suppresses the multiplication of cancer cells and induces apoptosis (3)(4)(5). EGCG suppressed adhesion and invasion of hepatocarcinoma cells through antioxidant activity (6).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have revealed that apoptosis functions in normal embryonic development (Brill et al, 1999;Lotz et al, 2006;Weingaertner et al, 2006), induction of excessive apoptosis by mechanistically diverse teratogens in early embryos leads to developmental injury (Chan, 2006(Chan, , 2007(Chan, , 2011Detmar et al, 2006;Hsuuw et al, 2005;Huang et al, 2003;Shang & Wu, 2004). EGCG has been shown to induce apoptosis (Kawai et al, 2005;Li et al, 2013). Data from the present study showed that EGCG suppresses embryonic cell proliferation during the blastocyst stage predominantly by apoptosis induction in the ICM and trophectoderm (TE).…”
Section: Introductionmentioning
confidence: 58%